Livestock production, politics and trade: A glimpse from Iron Age and Roman Languedoc. (April 2020) - Nieto-Espinet, Ariadna; Valenzuela-Lamas, Silvia; Bosch, Delphine; Gardeisen, Armelle
Highlights: Cattle and caprine mobility was assessed at two IA and Roman sites in S. France. Archaeological, zooarchaeological and strontium isotopic data were integrated. Strontium data suggest different mobility patterns in the Iron Age and Roman times. Local mobility is consistent with inbreeding pathologies and size reduction attested during IA. The results suggest that the socio-political system conditioned animal husbandry in this area. Abstract: Mobility is crucial in animal husbandry to overcome scarcity of food and the related over-grazing of pastures. It is also essential to reduce the inbreeding rate of animal populations, which is known to have a negative impact on fertility and productivity. Complex societies with a strong territorial component developed during the Iron Age in Southern France and across Europe. The impact of this phenomenon over animal husbandry is not yet fully understood, but a general small size of animals is attested in different parts of Europe at that time. This paper presents the main zooarchaeological results (main domesticates species representation, mortality profiles, osteometry, pathologies) of two major Iron Age sites in Languedoc – La Monédière (Bessan) and Lattara (Lattes). In addition, the strontium isotopic ratios ( 87 Sr/ 86 Sr) of 44 sheep and 16 cattle teeth from these sites are provided together with some baseline isotopic data. La Monédière and Lattara represent good case studies to characterise the geographic range of meat provisioning in coastal urban centres in the mid Iron Age (6th–4th c. BC). Their archaeological record enables us to analyse whether different species may have had different mobility patterns. In addition the strontium ratios of 4 Roman cattle from these sites were analysed for comparative purposes. The results are contextualised with other archaeological and zooarchaeological data from Languedoc and neighbour Catalonia, and suggest that the socio-political context has a major influence on animal production.